Análise do comportamento social do peixe-zebra: uma abordagem sobre respostas do tipo ansiedade e nocifensivas - Rosa, Luiz Vinícius Costa da (2022)
Social behavior plays a key adaptative role in several species on animal kingdom. Due to the biological role of this behavior, the use of social animal, such as the zebrafish (Danio rerio), represents a strategy to understand the biological processes associated which sociability. Aiming to elucidate how social behavior are affected by different contexts, we characterized the neurobehavioral responses in the presence of modulators of anxiety and nociceptive stimuli. In first paper, we developed a new three-dimensional (3D) analysis methodology of the shoal spatial occupation and investigated the behavioral changes induced byconspecific alarm substance (CAS), caffeine (CAF) (anxiogenic substances) and diazepam (anxiolytic substance). Behavioral 3D analyses revealed that both CAS and CAF decreased the shoal volume, average fish distance to the centroid point, and increased geotaxis, but only CAS reduced the inter-fish distance when compared to control (CTRL). Conversely, DZP group showed increased shoal volume and inter-fish distance. Thus, these data revels the importance of 3D analyses to represent the spatial occupation of zebrafish groups. In a second study, using the 3D developed protocol, we investigated the effects of nocifensive behavior on zebrafish social responses. For this purpose, we analyzed the behaviors before and after an intraperitoneal injection (i.p.) of phosphate-buffered saline (PBS) (CTRL), acetic acid 5% (AA), morphine 2.5 mg/kg (MOR) or acetic acid 5% plus morphine 2.5 mg/kg (AA+MOR) in only one subject from a four-fish shoal. Furthermore, we tested the social preference to PBS-, AA-treated shoals, or empty aquarium. In general, AA administration disrupted the shoal homogeneity, by eliciting dispersion of manipulated fish and clustering of non-manipulated fish. Moreover, morphine coadministration protected against AA-induced behavioral changes. Social preference test revealed a markedly preference to PBS shoals over AA. Therefore, this second study shows that the nociception can modulate zebrafish sociability. Overall, our findings presented here demonstrate the plasticity of the zebrafish social behavior as an adaptative defensive behavior. Altogether, the current thesis can support behavioral analysis methodology refinement, as well as the welfare of this specie in laboratorial facilities.